Firearms: Ownership, Laws & and The Case for Community Mobilization - Muhiuddin Haider; Jared Frank (International Journal of Public Health Science (IJPHS), 2014)
The United States (U.S.) currently ranks number one in the world in both the quantity of privately owned guns and the rate of private gun ownership. These privately owned firearms, which include rifles, shotguns and handguns, are predominantly owned by middle-aged, 35-54, white men, but the gaps have been steadily closing over the years, especially depending on the type of firearm, in all areas including gender, age, race, education level, political affiliation and geographic location. Gun violence is a leading cause of injury death in the U.S. In examining gun violence and potentially reducing its incidence, this article reviews gun ownership, access and utilization in the U.S., outcomes of gun violence, and the impact of community involvement in reducing gun violence. Specific areas of focus include the current state of background checks, with a focus on mental illness, and the role of medical professionals in guiding gun policy development. Gun violence continues to negatively impact the safety of individuals, families and communities. This article will emphasize the importance of social mobilization in enacting meaningful changes in gun policy and the development of relationships among healthcare professionals, social workers, and community members so as to further reduce and/or prevent gun violence.